2018
DOI: 10.1002/cptc.201800157
|View full text |Cite
|
Sign up to set email alerts
|

Solar Water Oxidation by a Visible‐Light‐Responsive Tantalum/Nitrogen‐Codoped Rutile Titania Anode for Photoelectrochemical Water Splitting and Carbon Dioxide Fixation

Abstract: Non‐oxide materials such as oxynitrides are good candidates as photoanodes for visible‐light‐driven water oxidation, but most of them suffer from oxidative degradation by photogenerated holes, resulting in low stability. Herein we developed a photoanode using a visible‐light‐responsive TiO2 powder doped with tantalum and nitrogen (TiO2:Ta/N) for water oxidation. The Ta/N codoping enabled a stable anodic photocurrent response attributable to water oxidation under visible‐light irradiation. Surface modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…To construct highly active Z‐scheme water‐splitting photocatalysts, the charge separation efficiency in the DSP must be improved, and the selective recognition of oxidized or reduced mediators is important for achieving one‐way electron transfer from the oxygen evolution photocatalyst to hydrogen evolution photocatalyst. Although most studies of DSPs have been conducted in the presence of sacrificial electron donators to promote the water‐splitting half reaction, [30–35] there have been several reports concerning water reduction or overall water splitting in the presence of redox‐reversible electron mediators [36, 37] . In 1993, Mallouk and co‐workers achieved an apparent quantum yield (AQY) of 0.3 % using a Ru II photosensitizer (PS) immobilized on the surface of a water reduction catalyst, Pt/H x K 4− x Nb 6 O 17 , with iodide as a redox‐reversible electron donor [38] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To construct highly active Z‐scheme water‐splitting photocatalysts, the charge separation efficiency in the DSP must be improved, and the selective recognition of oxidized or reduced mediators is important for achieving one‐way electron transfer from the oxygen evolution photocatalyst to hydrogen evolution photocatalyst. Although most studies of DSPs have been conducted in the presence of sacrificial electron donators to promote the water‐splitting half reaction, [30–35] there have been several reports concerning water reduction or overall water splitting in the presence of redox‐reversible electron mediators [36, 37] . In 1993, Mallouk and co‐workers achieved an apparent quantum yield (AQY) of 0.3 % using a Ru II photosensitizer (PS) immobilized on the surface of a water reduction catalyst, Pt/H x K 4− x Nb 6 O 17 , with iodide as a redox‐reversible electron donor [38] .…”
Section: Introductionmentioning
confidence: 99%
“…Althoughm ost studies of DSPsh ave been conducted in the presence of sacrificial electron donators to promote the water-splittingh alf reaction, [30][31][32][33][34][35] there have been several reports concerning water reduction or overallw ater splitting in the presence of redox-reversible electron mediators. [36,37] In 1993,M allouk and co-workers achieveda na pparentq uantum yield (AQY) of 0.3 %u sing aR u II photosensitizer (PS) immobilized on the surface of aw ater reduction catalyst, Pt/ H x K 4Àx Nb 6 O 17 ,w ith iodide as ar edox-reversible electron donor. [38] In 2013, Abe et al reported overall water splitting (AQY = 0.05 %) using coumarin derivatives( NKX-2677) immobilized on Pt/H x K 4Àx Nb 6 O 17 as aw ater reductionD SP coupled with an O 2 evolution photocatalyst comprising IrO 2 -Pt/WO 3 and iodide redox mediator.…”
Section: Introductionmentioning
confidence: 99%
“…Further research will be needed for elucidation of the reaction mechanism (e. g., investigation of the change in the valence state and local structure of Co 2 + and Al 3 + during the water oxidation reaction). We believe that in situ (or operando) XAFS measurement [41] is one of the candidates to clarify it, and will be performed as part of our future works.…”
Section: Resultsmentioning
confidence: 99%
“…Combining the RuRu' with a visible-light-absorbing semiconductor that has strong oxidation ability enables one to accomplish CO 2 reduction even with the use of a weak electron donor [7]. In some photoelectrochemical systems constructed from a similar binuclear metal complex and a semiconductor, sacrificial reagent-free CO 2 reduction has been achieved [9][10][11]. As these hybrid systems are based on the combination of photocatalysis of semiconductors and molecules, it is important to develop both of the two in harmony.…”
Section: Introductionmentioning
confidence: 99%